1998
DOI: 10.1074/jbc.273.52.35250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transmembrane and Kinase Domain Mutations on Fibroblast Growth Factor Receptor 3 Chimera Signaling in PC12 Cells

Abstract: The effect of six point mutations causing various human skeletal dysplasias, occurring in the transmembrane (TM) and kinase domains (KD) of fibroblast growth factor receptor 3, were introduced into a chimera composed of the extracellular domain of human platelet-derived growth factor ␤ and the TM and intracellular domains of hFGFR3. Stable transfectants in rat PC12 cells showed distinct differences in the two classes of mutations. The cells containing TM mutants displayed normal expression and activation but h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 47 publications
4
48
0
Order By: Relevance
“…The mutated residue 540 in FGFR3 is located in the proximal kinase domain (tyrosine kinase 1) within the ATP-binding domain and confers weak constitutive activation. Biochemical studies have shown that the mutation of the N540 residue to lysine in HCH results in weak ligand-independent autophosphorylation of an immature receptor protein (25). The crystal structure of FGFR1 suggests that the side chain of N546 is hydrogen-bonded to the main chain of H541 (22).…”
Section: Germline Mutations At Paralogous Positions In Fgfr2 and Fgfr3mentioning
confidence: 99%
“…The mutated residue 540 in FGFR3 is located in the proximal kinase domain (tyrosine kinase 1) within the ATP-binding domain and confers weak constitutive activation. Biochemical studies have shown that the mutation of the N540 residue to lysine in HCH results in weak ligand-independent autophosphorylation of an immature receptor protein (25). The crystal structure of FGFR1 suggests that the side chain of N546 is hydrogen-bonded to the main chain of H541 (22).…”
Section: Germline Mutations At Paralogous Positions In Fgfr2 and Fgfr3mentioning
confidence: 99%
“…Gain of function mutations in the tyrosine kinase domain of FGFRs are responsible for a number of human skeletal disorders. The degree of clinical severity associated with the mutations correlates with the level of constitutive kinase activity in these mutants (23)(24)(25). A method for rapidly comparing phosphorylation sites on various mutants of FGFRs and then correlating phosphorylation status with receptor activity would be very useful for understanding the molecular basis for receptor gain of function and potentially facilitate development of therapeutic interventions.…”
Section: Molecular and Cellular Proteomics 4:809 -818 2005mentioning
confidence: 99%
“…For instance, the Gly380Arg mutation in FGFR3 results in constitutive activation of the receptor in the absence of ligands in 3T3 (fibroblast), L6 (myoblast) and C2-7 (myoblast) cells (67;106), but not in 293 (kidney), PC12 (adrenal), and RCJ (chondrocyte) cells (106)(107)(108). An increase in phosphorylation due to the Gly375Cys FGFR3 mutation was observed in 293 cells, but not in PC12 cells (69;109).…”
Section: Cellular Studies: Effects On Downstream Signalingmentioning
confidence: 99%